Farmer participation in research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Farrington J and A Mann 1988 Farmer Participation in Agricultural Research: a review ot concepts and practices. O.D.I. 80pp UKL4 95 ISBN 085003 115X